Pengaruh Model Pembelajaran Inkuiri terhadap Hasil Belajar Siswa pada Subtema 2 Di Kelas III SD Negeri 091316 Pematang Raya - Rade Mancauli Sipayung; Lisbet N. Sihombing; Eva Pasaribu (Medan Resource Center, 2022)
This research purpose is to know the effect of inquiry model to study result students, the types of research of experiment with quasi design a give pre-test and post-test. This research do the class III in SD Negeri 091316 Pematang Raya .where experiment class used learning inquiry class while in control class used conventional model. Where the analysis data can find by an application program SPSS statistics 21.0 and Microsoft excel application. Based on explain above the analysis data result research find result T-test where the t-test >t-table namely 3,204 >2,010 with counting score significant (2-tailed)<0,05.sothat find the different experiment class with control class. Can see by score significant (2-tailed) = 0,002 < 0,05. So, Ho can say not significant and Ha significant. Based the result can conclude that the effect of model learning inquiry to study result students in Subtema 2 class III SD Negeri 091316 Pematang Raya. The improving presentation study result to learning give with used learning model inquiry and study result students the use learning model conventional is 13%